Analisis Aktivitas Antioksidan Ekstrak Daun Katang-Katang (Ipomea pes caprae) dengan Metode DPPH : Literature Review - Tsania Zahra Taslima; Zulpakor Oktoba; Atri Sri Ulandari; Muhammad Iqbal (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Free radicals are reactive molecules that contribute to oxidative stress, triggering cellular damage and leading to degenerative diseases such as cancer, diabetes, and cardiovascular diseases. Antioxidants are required to neutralize free radicals and protect the body from oxidative damage. The leaves of Ipomoea pes-caprae (L.) R. Br. contain secondary metabolites, such as flavonoids and phenolics, which have potential antioxidant activity. This article aims to analyze the antioxidant activity of Ipomoea pes-caprae leaf extract using the DPPH method. The study employed a literature review approach using Google Scholar with specific keywords and 13 articles met the inclusion criteria with a publication range from 2015 to 2025. The findings indicate that the extraction method and type of solvent significantly affect the effectiveness of antioxidant activity. Maceration and Soxhlet extraction methods were effective in isolating active compounds, particularly flavonoids and phenolics, while polar solvents such as ethanol and methanol produced better results compared to non-polar solvents. Antioxidant strength, determined by IC50 values, ranged from very strong to very weak. Therefore, it can be concluded that selecting the appropriate extraction method and solvent is crucial to maximizing the antioxidant potential of Ipomoea pes-caprae leaves as a natural antioxidant source for health and pharmaceutical applications.